Radiosynthesis and in vitro evaluation of 1-(tetrahydro-5-hydroxy-6-(hydroxymethyl)-2H-pyran-3-yl)-5-[I-125]iodour acil: A new potential agent for HSV1-tk reporter gene monitoring - Jo, Nam Hyun; Kim, Jung Young; El-Gamal, Mohammed I.; Choi, Won-Kyoung; Park, Jin-Hun; Kim, Eun Jung; Cho, Jung-Hyuck; Ha, Hyun-Joon; Choi, Tae Hyun; Oh, Chang-Hyun (WILEY-BLACKWELL, 2011)
Synthesis, radiolabelling, and in vitro evaluation of a new I-125-labelled iodouracil hexitol nucleoside analogue are reported. The target compound was successfully synthesized by an iodination-destannylation method and then purified by reverse phase HPLC. The radiochemical purity of the product was >99% with decay-corrected yields of 48 +/- 3%. In vitro cellular uptake testing was carried out using MCA and MCA-tk cell lines for comparison of compound 1 with [F-18] FHBG. The newly synthesized compound 1 showed higher accumulation in herpex simplex virus type 1 thymidine kinase (HSV1-tk) gene expression cell line (MCA-tk cell line) than in the wild type MCA cell line compared with [18 F] FHBG. The MCA-tk to MCA cellular uptake ratio for compound 1 was higher than that of [F-18] FHBG from 2 h after incubation. The radioiodine-labelled compound 1 (I-125, t(1/2) = 59.37 days) has a longer physical half-life than F-18-(t(1/2) = 110 min) labelled FHBG. Radioiodine-labelled compound 1 could be used for monitoring gene expression for a long time. The selectivity for MCA-tk cell line makes compound 1 a promising imaging agent for HSV1-tk expression.
Keywords: THYMIDINE KINASE GENE; PET IMAGING AGENT; EXPRESSION; THERAPY; FIAU; NUCLEOSIDES; ANALOGS; PROBES; SUGAR; FHPG